2018
DOI: 10.1158/1541-7786.mcr-18-0012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signature and Mechanisms of Hepatitis D Virus–Associated Hepatocellular Carcinoma

Abstract: There is limited data on the molecular mechanisms whereby hepatitis D virus (HDV) promotes liver cancer. Therefore, serum and liver specimens obtained at the time of liver transplantation from well-characterized patients with HDV-HCC ( = 5) and with non-HCC HDV cirrhosis ( = 7) were studied using an integrated genomic approach. Transcriptomic profiling was performed using laser capture-microdissected (LCM) malignant and nonmalignant hepatocytes, tumorous and nontumorous liver tissue from patients with HDV-HCC,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 36 publications
(49 reference statements)
1
52
0
Order By: Relevance
“…However, plasma levels of HDV‐RNA may fluctuate over time spontaneously, making it difficult to assess the association with disease outcome. Multiple molecular mechanisms are involved in the pathogenesis of HDV induced liver disease and cancer, which include imbalance in some genes activation in tumour tissue, activation of oxidative and DNA methylation pathways and possibly HBV genome deletions …”
Section: Discussionmentioning
confidence: 99%
“…However, plasma levels of HDV‐RNA may fluctuate over time spontaneously, making it difficult to assess the association with disease outcome. Multiple molecular mechanisms are involved in the pathogenesis of HDV induced liver disease and cancer, which include imbalance in some genes activation in tumour tissue, activation of oxidative and DNA methylation pathways and possibly HBV genome deletions …”
Section: Discussionmentioning
confidence: 99%
“…In this study, we extract raw expression data of 30 datasets, where 29 transcriptome datasets were obtained from GEO and one is from TCGA; each dataset contains at least 10 samples. The following is the list of datasets obtained from GEO: GSE102079 (Chiyonobu et al, 2018), GSE22405, GSE98383 (Diaz et al, 2018), GSE84402 (Wang et al, 2017), GSE64041 (Makowska et al, 2016), GSE69715 (Sekhar et al, 2018), GSE51401, GSE62232 (Schulze et al, 2015), GSE45267 (Chen et al, 2018a), GSE32879 (Oishi et al, 2012), GSE19665 (Deng et al, 2010), GSE107170 (Diaz et al, 2018), GSE76427 (Grinchuk et al, 2018), GSE39791 (Kim et al, 2014), GSE57957 (Mah et al, 2014), GSE87630 (Woo et al, 2017), GSE46408, GSE57555 (Murakami et al, 2015), GSE54236 (Villa et al, 2016;Zubiete-Franco et al, 2019), GSE65484 (Dong et al, 2015), GSE31370 (Seok et al, 2012), GSE84598, GSE89377, GSE29721 (Stefanska et al, 2011), GSE14323 (Mas et al, 2009), GSE25097 (Lamb et al, 2011;Tung et al, 2011;Wong et al, 2016), GSE14520 (Roessler et al, 2010;Zhao et al, 2015), GSE36376 (Lim et al, 2013), GSE36076). All GEO datasets were obtained using GEOquery package of Bioconductor in R-3.5.3.…”
Section: Collection Of Gene Expression Datasets Of Hccmentioning
confidence: 99%
“…2,3 That said, the fact that HDV does not integrate into the host cell genome does not exclude its direct oncogenic potential and experimental data indeed support a potential hepatocarcinogenic role of HDV antigens and a specific molecular signature of HDV-associated HCC. 4,5 The demonstration of a potential specific oncogenic role of HDV in human infection is only possible using robust cohort study designs where cirrhosis is no longer a confounder. In our analysis, only 1 cohort study accounted for cirrhosis as a confounder and found a significant hazard ratio of 2.1 for HCC in HDV-infected patients, independently of cirrhosis (which, nonsurprisingly, was itself found to be associated with HCC development).…”
Section: To the Editormentioning
confidence: 99%